Penentuan Tissue Aroma Terapi "Upik Abu" (Untuk Penyelamat Bumi Kita Terbuat dari Ampas Tebu) - Fauziah, Nuraini; Istikhomah, Novita; Verrysaputro, Exwan Andriyan; Puspawati, Andina (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Entrepreneurship Student Creativity Program (the PKM-K) of Tissue"Upik Abu" (Made From Sugar Cane Dregs To Save Earth) isdue tothe desireto targetopportunities ofincreased need fortissue. It alsomotivated the desire to produce tissue without cutting downthe treeas an effort tosave the environment, as well as utilization of bagasse which is usually only used as fuel for locomotives. This program is aimed to: (1) produce Tissue Aroma Therapy, (2) developa marketing strategy, and (3) getthe sales profit. Overview of effort in the PKM-K is producing tissue through cooperation with partners, introducing, and selling products of tissue "Upik Abu". Stage of implementation of its activities, namely market surveys, production, and marketing survey was conducted to get an overview of market potency. The production process consists of three stages, namely preparation, execution, and finishing. Tissue which is produced in the form of facial tissue, toilet tissue, and the tissue at the dinner table. The process of marketing is done through printed media (business cards, leaflets, mass-media), electronic media (facebook, twitter, blogs, SMS), community, exhibition, and consignment with some grocery stores. Aroma therapy is added to the tissue to be more marketable as well as comfortable to use. Tissue production has reached 650 units, with sales profit for three months of Rp. 3,862,500. Based on the results obtain edit can be concluded that the business is profitable, so the continuity of business will continue to be maintained, along with efforts to increase profits.Keywords : bagasse, tissue, aromatherapy